Digitizing Professional Zakat Through Payroll Systems: A Maqashid Shariah-Based Approach to Achieving the SDGs - Mustaqim, Dede Al; Toto Suharto; Afif Muamar (Jurnal Internasional Ekonomi Islam, 2025)
Introduction: Professional zakat is an Islamic financial instrument contributing to economic redistribution and poverty alleviation. In Indonesia, professional zakat has been accommodated in various regulations, including in PT PLN, which applies automatic deduction through the payroll system based on Board of Directors Regulation Number 120.P/DIR/2017. Objective: This study aims to analyze the implementation of professional zakat through the payroll system at PT PLN, from a maqashid sharia perspective, and its impact on achieving the Sustainable Development Goals. Method: This research used a qualitative approach with a case study method, involving interviews, observation, and document analysis. Result: This study found that professional zakat in PT PLN is automatically deducted by the payroll system by the Human Capital Management Division from the salaries of Muslim employees according to the nishab and managed by the PLN Baitul Maal Foundation. This implementation facilitates the obligation of zakat and follows the principles of maqashid sharia, and contributes to poverty reduction, education, and economic empowerment in achieving Sustainable Development Goals. Implication: This research shows that the payroll system in professional zakat ensures sharia compliance, contributes to social welfare, and accelerates the sustainable achievement of the Sustainable Development Goals.